Tradisi Her Tutu (Kawin Paksa) dalam Tatanan Hukum Adat Suku Kemak Kampung Sadi Kabupaten Belu Ditinjau dari Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual - Maritha Almeida Soares Fahik; Karolus Kopong Medan; Daud Dima Tallo (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
Legal protection for the tradition of forced marriage has been regulated in the form of Law Number 12 of 2022 concerning criminal acts of sexual violence. With the enactment of Law Number 12 of 2022, it guarantees legal certainty for victims of forced marriage in protecting their rights. The purpose of this research is to determine the essence of the "Her Tutu" (Forced Marriage) tradition and to determine the categorization of the "Her Tutu" (forced marriage) tradition. This research uses a type of socio-legal research, using an empirical approach, namely an approach based on the type of data and data analysis. The data used includes primary and secondary data, data collected through interviews and observations. Also, using data analysis by transcribing and compiling data systematically. From the research results it can be concluded (1) This tradition is based on family values and community unity. Marriage is seen as a way to strengthen relationships between families and maintain social harmony. (2) The tradition of her tutu forced marriage in the customary law of the Kemak tribe in Belu Regency. can be categorized as a criminal offense according to the sexual violence crime law contained in Article 10 of the Sexual Violence Crime Law. Based on conclusions. suggestions that can be given (1) Loss of individual autonomy and rights in determining their marriage. (2) Forced marriage is included in one type of criminal act of sexual violence (seen from Article 10 Paragraph (1) of Law Number 12 of 2022 concerning criminal acts of violence sexual.